Mechanistic peculiarities of activation-induced mobilization of cytotoxic effector proteins in human T cells. (24th January 2018) - Lettau, Marcus; Armbrust, Fred; Dohmen, Katharina; Drews, Lisann; Poch, Tobias; Dietz, Michelle; Kabelitz, Dieter; Janssen, Ottmar
Abstract: It is widely accepted that cytotoxic T and NK cells store effector proteins including granzymes, perforin and Fas ligand (FasL) in intracellular granules, often referred to as secretory lysosomes. Upon target cell encounter, these organelles are transported to the cytotoxic immunological synapse, where they fuse with the plasma membrane to release the soluble effector molecules and to expose transmembrane proteins including FasL on the cell surface. We previously described two distinct species of secretory vesicles in T and NK cells that differ in size, morphology and protein loading, most strikingly regarding FasL and granzyme B. We now show that the signal requirements for the mobilization of one or the other granule also differ substantially. We report that prestored FasL can be mobilized independent of extracellular Ca 2+, whereas the surface exposure of lysosome-associated membrane proteins (Lamps; CD107a and CD63) and the release of granzyme B are calcium-dependent. The use of selective inhibitors of actin dynamics unequivocally points to different transport mechanisms for individual vesicles. While inhibitors of actin polymerization/dynamics inhibit the surface appearance of prestored FasL, they increase the activation-induced mobilization of CD107a, CD63 and granzyme B. In contrast, inhibition of the actin-based motor protein myosin 2a facilitates FasL-, but impairs CD107a-, CD63- and granzyme B mobilization. From our data, we conclude that distinct cytotoxic effector granules are differentially regulated with respect to signaling requirements and transport mechanisms. We suggest that a T cell might 'sense' which effector proteins it needs to mobilize in a given context, thereby increasing efficacy while minimizing collateral damage.